Large vestibular aqueduct syndrome - Dipak, S.; Prepageran, Narayanan; Sazila, A.S.; Omar, Rahmat; Raman, R. (Malaysian Medical Association, 2005)
Large Vestibular Aqueduct Syndrome is a congenital malformation of the temporal bone characterised by early onset of sensorineural hearing loss and vestibular disturbance. Familial large vestibular aqueduct syndrome suggests autosomal recessive or X-linked inheritance and accounts for non-syndromic sensorineural hearing loss in these patients.